The Effect of Current Ratio, Total Asset Turnover, and Debt Asset Ratio on Return on Assets of Indonesian Food and Beverages Industry in 2019 - 2023 - Suryaningsih, Adhila; Rizwana, Zahra Ardya; Nareswari, Anindya Najmina (West Science Accounting and Finance, 2025)
This study examines the effect of the Current Ratio (CR), Total Asset Turnover (TATO), and Debt to Asset Ratio (DAR) on Return on Assets (ROA) in the food and beverage subsector companies listed on the Indonesia Stock Exchange during 2019-2023. The study uses panel data from 15 companies. The Fixed Effect Model (FEM) regression analysis shows that, simultaneously, all three variables significantly affect ROA. However, only TATO and DAR have a significant partial effect, while CR does not. These findings highlight the importance of asset efficiency and capital structure management in improving company profitability.